Family Narrative in the Illustrated Chronicle of Ivan the Terrible - M.S. Stepanova (Язык и текст, 2024)
This article aims to examine the family narrative in the Illustrated Chronicle of Ivan the Terrible. The study has enabled us to point out the following key topics in the context of family narrative: the marriage, the birth of children, the second marriage. The results allow us to say that the family representation in the chronicle corresponds with a Christian notion of marriage, i.e. the family is represented as a union of a man and a woman in which a man is the head of the family and a woman is mother of a multi-child family standing behind her husband. Procreation is one of the key goals of marriage and a great joy. The chronicle touches upon the issue of the second marriage of Russian rulers, and the second marriage conforms with the traditions of the time and the Church rules.